2021
DOI: 10.3390/antiox10030394
|View full text |Cite
|
Sign up to set email alerts
|

The Phenoxyphenol Compound diTFPP Mediates Exogenous C2-Ceramide Metabolism, Inducing Cell Apoptosis Accompanied by ROS Formation and Autophagy in Hepatocellular Carcinoma Cells

Abstract: Hepatocellular carcinoma (HCC) is a severe disease that accounts for 80% of liver cancers. Chemotherapy is the primary therapeutic strategy for patients who cannot be treated with surgery or who have late-stage HCC. C2-ceramide is an effective reagent that has been found to inhibit the growth of many cancer types. The metabolism of C2-ceramide plays a vital role in the regulation of cell death/cell survival. The phenoxyphenol compound 4-{2,3,5,6-tetrafluoro-4-[2,3,5,6-tetrafluoro-4-(4-hydroxyphenoxy)phenyl]phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…What is more, Wang et al demonstrated that EPS364, a deep-sea bacterial exopolysaccharide, exhibited an antitumor trait by inducing hepatic cell death by upregulating ROS production, supporting the idea that oxidative stress could trigger cell death [45]. And the idea is likewise proofed by another research where diTFPP/C2-ceramide increased hepatic cell death by increasing ROS levels [39]. Evidence has shown that the inhibition of ROS production can alleviate abnormal cell death.…”
Section: Irisin Decreases Er Stressmentioning
confidence: 90%
See 1 more Smart Citation
“…What is more, Wang et al demonstrated that EPS364, a deep-sea bacterial exopolysaccharide, exhibited an antitumor trait by inducing hepatic cell death by upregulating ROS production, supporting the idea that oxidative stress could trigger cell death [45]. And the idea is likewise proofed by another research where diTFPP/C2-ceramide increased hepatic cell death by increasing ROS levels [39]. Evidence has shown that the inhibition of ROS production can alleviate abnormal cell death.…”
Section: Irisin Decreases Er Stressmentioning
confidence: 90%
“…It is found that autophagy participated in the repair of ROS-induced oxidative proteins in LO2 cells [38]. Chang et al found that the production of ROS was elevated in diTFPP/C2-ceramide-treated cells with the activation of autophagy, proving autophagy is involved in the oxidative processes [39]. The induction of autophagy also helps to suppress oxidative stress.…”
Section: Irisin Decreases Er Stressmentioning
confidence: 99%
“…Library construction and RNA sequencing (RNAseq) were performed by BIOTOOLS (Taipei, Taiwan) based on the manufacturer’s instructions [ 24 ]. In brief, the total RNA from zebrafish embryos treated with IS was analyzed by RNAseq using oligo(dT)-labeled magnetic beads.…”
Section: Methodsmentioning
confidence: 99%